THE IMPACT OF GAMIFIICATION ON THE TEACHING OF MATHEMATICS IN SECONDARY EDUCATION STUDENTS - Aily Diomara Morales Jaimes (DIALÉCTICA, 2025)
Mathematics teaching in secondary education faces numerous challenges, including student demotivation, a perception of the subject as difficult, and a lack of connection to real-life situations. These problems have led to the search for innovative strategies that foster more dynamic and effective learning. In this context, gamification has emerged as a promising alternative, based on the incorporation of game elements into educational environments with the aim of enhancing the learning experience. This article analyzes the current state of research on the impact of gamification on mathematics teaching and how it, in turn, can energize the classroom and foster the development of critical thinking and problem-solving skills. The methodology is guided by a bibliographic review of articles and research conducted over the past five years (2020-2025) using databases such as Google Academic, Redalyc, and SciELO. It should be noted that the studies reviewed were conducted in Latin America, including those conducted within the established time frame, in Spanish, and focused on secondary school students. The results show multiple studies demonstrating that gamification has a positive impact on mathematics teaching, fostering student motivation, commitment to learning, and improved academic performance. Furthermore, the studies analyzed highlight that incorporating playful elements in the classroom contributes to the development of critical thinking and problem-solving, while allowing for greater student interaction and more meaningful learning. However, challenges in its implementation are also identified, such as the need for teacher training in the design of gamified strategies and the adaptation of curricular content to this methodology.